(untitled) - Mather, Peter (Boston, Mass., 2003)
Designed to help students become jazzed about reading, this introductory-to-intermediate reading text provides motivating and engaging readings selected to grab the reader's attention. Reading and All That Jazz also features clear explanations and a wide variety of well-developed practice exercises designed to provoke genuine thinking, interpretation, and even some improvisation on the part of the student and the instructor. The theme of jazz emphasizes a positive, exciting, personally involved approach to reading and learning
Keywords: English language,Study skills,Reading (Higher education),Trung tâm Học liệu ĐHCT; Rhetoric,Đọc hiểu tiếng Anh; United States,United States